Aircraft Maintenance Engineering Higher Apprenticeship: Review and Challenges - Kasava, N K (KnE Social Sciences, 2018)
This article is a review paper to discuss the definition of apprenticeship and differentiation between apprenticeship scheme and school-based vocational education model for aircraft maintenance engineering. The author explores literature between years 2015 and 2017 related to apprenticeship. Besides academic literature, the author reviewed Australia, Malaysia, Indonesia and United Kingdom apprenticeship-related documents. This was to ensure that a rigor literature review was conducted prior further author’s review discussion. The author used observation and secondary government document archival data in this article. The author discussed the flow of an aircraft engineering apprenticeship programs conducted by legacy air carriers. The future trend has shifted aircraft engineering apprenticeship program from purely work-based vocation training to mix school-based vocational education training. This paradigm shift were driven by business outsourcing model, reduction airline training cost, technological change, digitizing aircraft and reduction of basic training equipment purchase and syllabus standardization across the industry. In conclusion the author recommended future agile apprenticeship integrated school-based vocational conceptual model for aircraft maintenance engineering apprenticeship program. This conceptual model was to overcome the current challenges of digitization industry, standardization of syllabus and skill. Keywords: apprenticeship, aircraft maintenance vocational education